Inovasi Badan Layanan Umum (BLU) dalam Meningkatkan Pendapatan di Masa Pandemi COVID-19 - Dani Sugiri (Program Studi Manajemen Fakultas Ekonomi UMRAH, 2022)
The COVID-19 pandemic has had a fairly severe impact on entities providing services to the community, including the Public Service Agency or Badan Layanan Umum (BLU). This study aims to describe the various innovations carried out by the Public Service Agency (BLU) to improve services and optimize Non-Tax State Revenue (PNBP). The research was conducted with a qualitative approach with data collection using literature studies and document analysis. The results of the study indicate that the innovations carried out by the BLU include (a) increasing the optimization of assets managed by the BLU; (b) implementation of the strategy for digitizing business processes and BLU services; (c) increasing the synergy of BLU services; and (d) cutting costs and tariffs for BLU services. This innovation is carried out in order to continue to provide the best service while still trying to achieve efficiency and productivity, even in the unfavorable conditions of the COVID-19 pandemic.